Evaluasi Kondisi Pariwisata Kawasan Wisata Gunung Galunggung - Dofi khaikal Arwani; Gina Puspitasari Rochman (UNISBA Press, 2022)
Abstract. The tourist area of Mount Galunggung is one of the leading natural tourist areas in Tasikmalaya Regency. This area will be developed into a geotourism area. Prior to development, it is necessary to evaluate the tourism condition in this area. This is because there are several problems that exist in the Mount Galunggung tourist area including the discovery of a large amount of garbage scattered about, the existence of vandalism by visitors, accessibility to the damaged Galunggung crater, and things that worsen the tourism situation due to the Covid-19 pandemic which resulted in the closure of the Mount Galunggung tourist area for some time and caused considerable losses for the tourist area. Therefore, the purpose of this study is